Intestinal parasitosis, undernutrition and socio-environmental factors in schoolchildren from clorinda formosa, Argentina - Zonta, Maria Lorena (2019)
Objective: To evaluate intestinal parasitosis, undernutrition and socio-environmental factors in schoolchildren from Clorinda (Formosa, Argentina). Materials and Methods: Serial fecal samples and anal swabs of 114 schoolchildren, canine feces and soil samples were analyzed. Body weight and height of 215 schoolchildren were measured and undernutrition was estimated according to the World Health Organization criteria. Socio-environmental variables were assessed by means of a semi-structured questionnaire. Results: 78.1% of children were infected by at least one of the 12 species identified and 70.8% had multiple parasitic infections. Blastocystis sp., Giardia lamblia and Enterobius vermicularis were the most prevalent. Additionally, 17.5% of children were infected by at least one geohelminth (e.g. Ascaris lumbricoides, Trichuris trichiura, hookworms). 64.3% of canine of canine feces were positive and six parasitic species were found; the most frequent were Ancylostoma caninum, Uncinaria stenocephala and G. lamblia. Furthermore, 37.5% of soil samples showed zoonotic parasites (i.e. Ascaris sp., Toxocara sp.). Finally, 10.0% of the children were undernourished and 85.7% of them had parasites. The risk for parasitosis was higher in children that lived in houses with inadequate solid waste disposal and whose parents were unemployed or had temporary jobs. Conclusions: The lack of environmental sanitation, unstable employment of parents and the presence of zoonotic species were the most relevant factors observed. Consequently, these conditions result in an increase of parasitic infections and negatively influence the growth of children.